(untitled) (Jurnal Pertanian Terpadu, 2019)
Pineapple plantations around Mount Kelud are pineapple producing centers in East Java. The most commonly planted is Queen, but 10-15% of the harvest is grade C which is smaller than other grades. This study aims to analyze the properties of the juice and juice concentrate of the pineapple Queen varieties grade C, and comparing it with those processed from grade B to determine whether or not there are differences in product properties. In the method, the products are first made, analyzed for their physicochemical properties, and compared using a comparative analysis t-test independent. Physicochemical analysis of juice made from grade C and grade B, results average value of TPT, water content, total sugar, total acid, viscosity, color La*b*, respectively: 15,90obrix and 15,97obrix; 83.27% and 83.73%; 14.98% and 13.96%; 1.01% and 1.08%; 5.00 cP and 2.33 cP; 23.63 and 23.73; 6.17 and 6.20; 9.53 and 9.03. The average of that properties in juice concentrate made from grade C and grade B, respectively: 63.40obrix and 63.57obrix; 31.80% and 33.53%; 57.95% and 61.39%; 2.63% and 2.50%; 293,00cP and 211,33cP; 25.93 and 25.27; 8.00 and 7.57; 13.33 and 12.57. The results of the t-test independent shows that all the tcount between (-) 4.604 to (+) 4.604 so that ho is accepted, which means there is no difference in the average physicochemical properties of pineapple juice Queen varieties grade C and grade B, and there is no difference in the average physicochemical properties of pineapple juice concentrate Queen varieties grade C and grade B